2015
DOI: 10.4046/trd.2015.78.4.336
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned Extubation in Patients with Mechanical Ventilation: Experience in the Medical Intensive Care Unit of a Single Tertiary Hospital

Abstract: BackgroundPotentially harmful unplanned extubation (UE) may occur in patients on mechanical ventilation (MV) in an intensive care unit (ICU) setting. This study aimed to evaluate the clinical characteristics of UE and its impact on clinical outcomes in patients with MV in a medical ICU (MICU).MethodsWe retrospectively evaluated MICU data prospectively collected between December 2011 and May 2014.ResultsA total of 468 patients were admitted to the MICU, of whom 450 were on MV. Of the patients on MV, 30 (6.7%) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
(46 reference statements)
2
11
1
1
Order By: Relevance
“…We found that 136 (46.1%) patients required reintubation within 48 hours after UE, and that the mortality rate of UE patients who required reintubation was higher than for patients who did not: 25.0% (34/136) vs. 6.9% (11/159). This is consistent with previous studies 14 , 20 , 26 . Overall, reintubation was associated with poorer outcomes in UE patients.…”
Section: Discussionsupporting
confidence: 94%
“…We found that 136 (46.1%) patients required reintubation within 48 hours after UE, and that the mortality rate of UE patients who required reintubation was higher than for patients who did not: 25.0% (34/136) vs. 6.9% (11/159). This is consistent with previous studies 14 , 20 , 26 . Overall, reintubation was associated with poorer outcomes in UE patients.…”
Section: Discussionsupporting
confidence: 94%
“…According to a previous study, nurse-driven sedation protocol is helpful in preventing adverse events [14]. Thus, the results of higher motor response scores and more likelihood of emergency admissions in the unplanned extubation group suggest that a sedation protocol is necessary and admission to the emergency group requires closer observation.…”
Section: Discussionmentioning
confidence: 93%
“…Endotrakeal entübasyon sonrasında gelişebilecek önemli bir komplikasyon olan PE, hastanın ventilatörden ayrılmasına ve hava yolu kontrolünü kaybetmesine yol açan bir durumdur (17). Weaning planlanmadan ekstübe olan hastaların oranı pek çok çalışmada %0,3 -16 arasında olarak bildirilmiştir (7,13,14,18). Bizim çalışmamızda PE oranı %6,7 idi.…”
Section: Discussionunclassified